2018
DOI: 10.3348/kjr.2018.19.5.897
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Preoperative Magnetic Resonance Imaging Features Associated with Positive Resection Margins in Breast Cancer: A Retrospective Study

Abstract: ObjectiveTo determine which preoperative breast magnetic resonance imaging (MRI) findings and clinicopathologic features are associated with positive resection margins at the time of breast-conserving surgery (BCS) in patients with breast cancer.Materials and MethodsWe reviewed preoperative breast MRI and clinicopathologic features of 120 patients (mean age, 53.3 years; age range, 27–79 years) with breast cancer who had undergone BCS in 2015. Tumor size on MRI, multifocality, patterns of enhancing lesions (mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 35 publications
0
18
0
2
Order By: Relevance
“…In past studies with study populations composed mostly of patients with IDC, NME on preoperative MRI, tumor size exceeding 5 cm, and multifocal lesions were factors associated with positive resection margins after BCS ( 9 27 28 ). As DCIS lesions commonly appear as NME on MRI ( 29 30 ), previous studies suggested an association between DCIS components and positive resection margins ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In past studies with study populations composed mostly of patients with IDC, NME on preoperative MRI, tumor size exceeding 5 cm, and multifocal lesions were factors associated with positive resection margins after BCS ( 9 27 28 ). As DCIS lesions commonly appear as NME on MRI ( 29 30 ), previous studies suggested an association between DCIS components and positive resection margins ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, these results were based on study populations composed mostly of patients with invasive ductal carcinoma (IDC) ( 9 10 ). Furthermore, the majority of malignant NME lesions depicted by MRI in previous studies were confirmed as DCIS, so the sensitivity advantage of MRI over conventional imaging in depicting local tumor extent was reported to increase as DCIS component size increased, which would be less frequently detected in invasive lobular carcinoma (ILC) ( 11 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the accurate determination of tumor margins in real time during surgical intervention has received significant attention 4 , 5 . Advanced technologies proposed to solve what has become known as “the margins problem” have included hyperspectral optical imaging 6 , magnetic resonance imaging 7 , and ultrasound 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Although background parenchymal enhancement (BPE) on breast MRI results from physiological enhancement in fibroglandular tissue, strong BPE may yield abnormal interpretation and false-positive biopsy results (14,15). Moderate to marked BPE is also associated with an inaccurate estimation of tumor size at preoperative staging MRI and has been associated with higher rates of positive resection margins (16)(17)(18)(19)(20). In general, BPE increases after a contrast agent is administered and is more prominent during the late phase than the early phase in DCE-MRI (19).…”
Section: Introductionmentioning
confidence: 99%